Virtually Sailing into Digital Ocean: An Ethnolinguistics Study on r/ Piracy Community - Ramadhan, Daffa (ETNOLINGUAL, 2024)
: The objective of the study is to examine the connection between language, and the dynamics of r/Piracy community. Therefore, the questions in this study are (1) What are the common nautical-related terms and expressions used within the r/Piracy community? (2) By using nautical-related terms, what kind of beliefs and values are reflected by the members of the r/Piracy community? This study employs a sociolinguistics approach that views language intertwined with societal norms. Therefore, Communalytic was used to gather the language used by both users and moderators of r/Piracy community in posts to form a corpus. Then, the nodes in the corpus are manually tagged with Sketch Engine. Additionally, a built-in network analyzer was used to examine the communication pattern to determine social activity. Finally, the author used Wardhaugh and Janet's theory of language variations. The corpus consists of 3,265 posts containing 103,117 words. The most frequent words found in this community are torrent (142), pirate (110), port (29), seas (17), ship (15), mate (13), sail (13), treasure (4), plunder (3), mate (3), adventure (2), map (2), and loot (1). This study reveals the importance of discussions related to file-sharing and torrenting, as evidenced by the high frequency of the term "Torrent" in the corpus. This research sheds light on the relationship between language and community dynamics in online spaces, emphasizing the role of language in shaping and expressing social identities and interests. The study contributes to our understanding of how language and sociaety intertwined within specific online communities, providing insights into the sociolinguistics aspect of r/Piracy subreddit. Keywords: Society, Digital Piracy, r/Piracy, Nautical-terms